BRIDGING THEORY AND PRACTICE: MODERN APPROACHES TO MOTHER TONGUE EDUCATION IN MALAYSIA - Ya , Ling Lew; Chee, Sie Ching (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
This study examines the challenges and potential solutions in mother tongue education in Malaysia, focusing on Dr. Huang Xian Bing’s innovative ideas and practices. Through literature review and case study analysis, the research explores the current landscape of mother tongue education in Malaysia, highlighting the overlooked role of children’s literature. The study reveals that Dr. Huang has introduced novel approaches, particularly through promoting children’s literature and reforming teaching methodologies. Key findings indicate that emphasizing children’s literature, reforming teaching methods, and strengthening connections between mother tongue and real-life experiences are crucial for improving education quality. These insights align with international trends while reflecting Malaysia’s unique multilingual context. This research offers valuable recommendations for policymakers and practitioners, contributing new perspectives on mother tongue education in multilingual societies.